The Role of Cardiac Arrest Sonographic Exam (CASE) in Predicting the Outcome of Cardiopulmonary Resuscitation; a Cross-sectional Study: Cardiac Arrest Sonographic Exam - Masoumi, Babak; Azizkhani, Reza; Heydari, Farhad; Zamani, Majid; Nasr Isfahani, Mehdi (Archives of Academic Emergency Medicine, 2021)
Introduction: Ultrasonography (US) has been suggested as an integral part of resuscitation to identify potentially reversible causes of cardiac arrest (CA). This study aimed to evaluate the association between cardiac activity on ultrasonography during resuscitation and outcome of patients with non-shockable rhythms. Methods: We conducted a prospective, observational study on adult patients presenting with CA or experiencing CA in the emergency department (ED), and initial non-shockable rhythm. US examination of the sub-xiphoid region was performed during the 10-second interval of rhythm and pulse check and the association of US findings and patients’ outcomes was evaluated. Results: 151 patients with the mean age of 65.32 ± 11.68 years were evaluated (76.2% male). 43 patients (28.5%) demonstrated cardiac activity on the initial US. The rate of asystole in initial rhythm was 58.9% (n=89). Return of spontaneous circulation (ROSC) was achieved in 36 (23.8%) patients, twenty (13.2%) survived to hospital admission and seven (4.6%) survived to hospital discharge. When the cardiac standstill duration increased to six minutes, no patient survived hospital discharge. Potentially reversible causes were detected in 15 cases (9.9%), and four of them survived to hospital discharge. Cardiac activity on first scan was associated with ROSC (OR: 6.86, 95%CI: 2.92-16.09; p < 0.001), survival to hospital admission (OR: 17.80, 95%CI: 3.95–80.17; p < 0.001), and survival to hospital discharge (OR: 17.35, 95%CI: 2.02–148.92; p = 0.001). Conclusion: In non-traumatic cardiac arrest patients with non-shockable rhythms, bedside US is of great importance in predicting ROSC. The presence of pulseless electrical activity (PEA) rhythm and cardiac activity on initial US were associated with ROSC, survival to hospital admission, and hospital discharge. When the cardiac standstill duration increased to six minutes, no patient survived hospital discharge.